Evaluating the effects of road hump on the speed of vehicles in an institutional environment - Rosli, Nur Najiah Azhani; Kadar Hamsa, Abdul Azeez (Eastern Asia Society for Transportation Studies, 2019)
Vehicles travelling at speed above the permissible speed limit have jeopardized the safety of road users. The concern is greater at institutional environment whereby most road users travel by walking. Road hump is considered as an efficient traffic calming measure in reducing the speed of the vehicle. This paper investigates the effects of different road hump dimensions in decreasing the speed of vehicles at the main road of International Islamic University Malaysia. Six (6) road humps with different design profile were selected. The design profile and spot speed of the vehicles at all six (6) road humps were measured. The speed of vehicles at the road hump was analyzed by using descriptive analysis and t-test. The findings of this study suggest that road hump is effective in lowering the speed of vehicles in an institutional environment. The dimensions of road hump, especially height, influence significantly the speed reduction of vehicles.